2016
DOI: 10.17221/405/2015-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient content of puffed proso millet (Panicum miliaceum L.) and amaranth (Amaranthus cruentus L.) grains

Abstract: Piłat B., Ogrodowska D., Zadernowski R. (2016): Nutrient content of puffed proso millet (Panicum miliaceum L.) and amaranth (Amaranthus cruentus L.) grains. Czech J. Food Sci., 34: 362-369.Puffed grains of the varieties of proso millet (Penicum miliaceum L.) and amaranth (Amaranthus cruentus L.) were evaluated as a source of nutritional compounds. The process of grain puffing was performed in prototype equipment of the "Szarłat" company. The analysed mean values for puffed grains were starch (proso millet 72.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The same properties for linseed were recorded by Goyal et al (2014). Elements found in large quantities in proso millet were phosphorus, potassium, magnesium (Pilat et al, 2016). The obtained data in the current study revealed that proso millet could be a good source of K and P. Buckwheat is seen as a dietary source of zinc, copper and manganese (Ikeda and Yamashita, 1994).…”
Section: Fatty Acid and Mineral Compositionsupporting
confidence: 74%
“…The same properties for linseed were recorded by Goyal et al (2014). Elements found in large quantities in proso millet were phosphorus, potassium, magnesium (Pilat et al, 2016). The obtained data in the current study revealed that proso millet could be a good source of K and P. Buckwheat is seen as a dietary source of zinc, copper and manganese (Ikeda and Yamashita, 1994).…”
Section: Fatty Acid and Mineral Compositionsupporting
confidence: 74%
“…Puffing and extrusion are usually performed at high temperatures for a short time. Pilat et al reported that puffed proso millet had a high polyphenol content and thus good nutritional properties (38). The TPC and TFC in extruded finger millet flour were significantly lower than unextruded checks with maximum retention rates of 54 and 78%, respectively (39).…”
Section: Heat Treatmentmentioning
confidence: 99%
“…The nutrient composition of proso millet was reported by Piłat et al [3]. The results showed that they had starch of 72.58%, fat 8.43%, proteins 13.89%, amino acids 48.30 g/Kg, crude fibre 4.29% and total polyphenol content of 0.98%.…”
Section: Introductionmentioning
confidence: 79%